Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1093/jaoac/88.3.800
|View full text |Cite
|
Sign up to set email alerts
|

Precise Method for the Measurement of Catalase Activity in Honey

Abstract: An improved method is reported for the determination of catalase activity in honey. We tested different dialysis membranes, dialysis fluid compositions and amounts, dialysis temperatures, sample amounts, and dialysis times. The best results were obtained by dialysis of 7.50 g sample in a cellulose dialysis sack, using two 3 L portions of 0.015M sodium phosphate buffer (pH 7.0) as the dialysis fluid at 4°C for 22 h. As in previous methods, catalase activity was determined on the basis of the rate of disappearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…About the peroxide component, glucose oxidase represents the main carbohydrate-metabolizing enzyme mainly added to nectar by bees during elaborating honey, which is responsible of the conversion of glucose into hydrogen peroxide (H 2 O 2 ) and gluconic acid under aerobic conditions [ 34 , 35 ]. Factors that affect H 2 O 2 accumulation are inactivation of the enzyme glucose oxidase by exposure to heat, light [ 36 , 37 ], or catalase [ 38 , 39 ]. Regardless, peroxide component is also present in nectar [ 40 ], and substantial variation in its accumulation among different nectar samples was observed [ 41 , 42 ].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…About the peroxide component, glucose oxidase represents the main carbohydrate-metabolizing enzyme mainly added to nectar by bees during elaborating honey, which is responsible of the conversion of glucose into hydrogen peroxide (H 2 O 2 ) and gluconic acid under aerobic conditions [ 34 , 35 ]. Factors that affect H 2 O 2 accumulation are inactivation of the enzyme glucose oxidase by exposure to heat, light [ 36 , 37 ], or catalase [ 38 , 39 ]. Regardless, peroxide component is also present in nectar [ 40 ], and substantial variation in its accumulation among different nectar samples was observed [ 41 , 42 ].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Catalase activity was measured according to Huidobro et al (2005) and expressed as Kf (catalase activity (min-1) per gram of honey).…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Factors known to affect H 2 O 2 accumulation are inactivation of the H 2 O 2 ‐producing enzyme glucose oxidase by exposure to heat or light (24, 25) or degradation of H 2 O 2 by honey (12, 26). It has been suggested that catalase originating from pollen, nectar, or microorganisms would be responsible for the enzymatic H 2 O 2 ‐neutralizing activity of honey (26, 27); however, to the best of our knowledge, catalase has never been identified in honey.…”
Section: Hydrogen Peroxidementioning
confidence: 99%